Job Displacement Costs of Phasing Out Coal - Juan Pablo Rud; Michael Simmons; Gerhard Toews; Fernando Aragon (Institute of Labor Economics (IZA), 2022)
The reduction of carbon emissions will require a rapid phasing out of coal and the displacement of millions of coal miners. How much could this energy transition cost mining workers? We use the dramatic collapse of the UK coal industry to estimate the long-term impact on displaced miners. We find evidence of substantial losses: wages fell by 40% and earnings fell by 80% to 90% one year after job loss. These losses are persistent and remain significantly depressed fifteen years later, amounting to present discounted value earnings losses of between four and six times the miners pre-displacement earnings.
Keywords: J30; J63; J64; O4; 330; labor displacement; energy transition; coal mines